Effect of compression ratio on the emission, performance and combustion characteristics of a gasoline engine fueled with iso-butanol/gasoline blends - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The study focuses on the effect of CR (compression ratio) on the emission, performance and, combustion characteristics of a gasoline engine fueled with iso-butanol (10%, 30% and 50%) blended gasoline fuel. The tests were conducted for three different CRs (9:1,10:1 and 11:1) at 2600 rpm and wide-open throttle. The results indicate that the BSCF (brake specific fuel consumption), BTE (brake thermal efficiency) and the emissions of CO2 (carbon dioxide) increased while UHC (unburned hydrocarbon) and CO (carbon monoxide) emissions decreased with the increase in the amount of iso-butanol in the fuel mixture at all CRs. The best results for BSFC, BTE, the emissions of CO and UHC were observed at increased the CR. Moreover, the ICP (in-cylinder pressure) generally increased with the increase in the amount of isobutanol in the fuel mixture and the ICP and HRR (heat release rate) rose earlier than those values in gasoline. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Exhaust emissions; Compression ratio; Iso-butanol; Engine performance; SPARK-IGNITION ENGINE; CONVERSION EFFICIENCY; DUAL INJECTION; BUTANOL; BIODIESEL; ETHANOL; BIOFUELS; PORT